Chapter Dal Desdén di Moreto ai Plaisirs di Molière - Lombardi, Marco (Studi e saggi, 2020)
In 1664 Molière and his troupe played in the gardens of Versailles, in front of the Sun King, La Princesse d'Elide a rewriting of the Desdén con el Desdén by Moreto. As Maria Grazia Profeti pointed out in her writings, Genette's analysis still allows, after some time from the critical works of the critic, to avoid the ever-present and threatening obstacles of moral, formal or aesthetic value judgements accompanied by the more or less declared idea of superiority or inferiority of an author or a culture and dramaturgy. Entering the Molierian laboratory, after having highlighted how much the French hypertext owes to its Spanish hypotext, the essay tries to recontextualize the pièce within the Royal Festivals of the Plaisirs de île enchantée also in the light of the reception of contemporaries: wearing virtually the spectacles of a spectator of the time, and taking into consideration the transvalorizations carried out by the French playwright, he also tries to grasp the meaning that the Molierian play may have assumed for the Sovereign and the public in the context of the political and sentimental biography of the King of France at that chronological height.